ANALISIS PERFROMANSI BILAH TAPERLESS HORIZONTAL AXIS WIND TURBINE (HAWT) MENGGUNAKAN AIRFOIL USA40 DAN USA35-B PADA TSD-500. (STUDI KASUS DI PT. LENTERA BUMI NUSANTARA) - Cahyani Putri Pangestu (2021)
The current state of world energy has turned towards renewable energy. There are many types of renewable energy in the world, one of which is wind energy. Wind energy is predicted to be one of the promising renewable energy sources in Indonesia. In converting wind energy into electrical energy, a windmill is used, namely a wind turbine in which there is one important component in the energy change process, namely the blade. The blade has a function as a converter of wind kinetic energy into mechanical energy which will later become mechanical energy to drive a generator to produce electrical energy. The blade with the taperless type can be used in both fast and slow wind conditions. Airfoil is part of the blade that causes a blade to have an aerodynamic force. In writing this thesis, the type of airfoil used is USA 40 and USA 35-. Testing in writing this thesis was carried out using a simulation method on BEM (Blade Element Momentum)-based software and also observations on field testing. The analysis was carried out on a turbine power of 500 watts, at varying wind speeds, 0.12 m wide blades, 3 blades, and a TSR of 7. The results of this test indicate that the two types of airfoil USA 40 have better performance than the USA. 35-B both in terms of simulation and direct field testing.